Determinants of Demand for Foreign Tourism in Indonesia - Mariyono, Joko (Universitas Muhammdaiyah Surakarta, 2017)
This study aims to analyze the determinants of foreign tourists visiting Indonesia. Tourism sector is important in Indonesian economy because it is one of potential sources of foreign exchange and promotes economic growth. Decrease in number of domestic tourists is not as important as foreign ones since the later can be a potential source of foreign exchange. Model of travel cost demand for tourism is estimated using panel data, consisting of 34 countries across the globe during 2004-2013. Data were compiled from Indonesian Statistical Agency and the World Bank database. The result shows that distance is a one of significant factors that reduces the number of foreign tourists coming to Indonesia. Bomb attack reduced the number of foreign tourists. Tourists from western and ASEAN countries were more likely to visit Indonesia than others. Indonesian policy should guarantee with security to tourists to attract more arrivals